2013
DOI: 10.5194/bg-10-5009-2013
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric turbulence triggers pronounced diel pattern in karst carbonate geochemistry

Abstract: Abstract. CO2 exchange between terrestrial ecosystems and the atmosphere is key to understanding the feedbacks between climate change and the land surface. In regions with carbonaceous parent material, CO2 exchange patterns occur that cannot be explained by biological processes, such as disproportionate outgassing during the daytime or nighttime CO2 uptake during periods when all vegetation is senescent. Neither of these phenomena can be attributed to carbonate weathering reactions, since their CO2 exchange ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 43 publications
3
64
0
Order By: Relevance
“…Roland et al . 52 used a chemical carbonate weathering model to explain non-biological fluxes detected at ecosystem scale in a karst, finding that the CO 2 coming from deeper layers at night could be stimulating carbonate dissolution and, thus, consuming CO 2 . Hamerlynck, et al ., 53 found a negative F soil at night in a Chihuahuan desert shrubland, both using an automatic soil chamber and using the gradient method with CO 2 sensors buried in the shallowest layer, similarly attributing the CO 2 consumption to carbonate dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…Roland et al . 52 used a chemical carbonate weathering model to explain non-biological fluxes detected at ecosystem scale in a karst, finding that the CO 2 coming from deeper layers at night could be stimulating carbonate dissolution and, thus, consuming CO 2 . Hamerlynck, et al ., 53 found a negative F soil at night in a Chihuahuan desert shrubland, both using an automatic soil chamber and using the gradient method with CO 2 sensors buried in the shallowest layer, similarly attributing the CO 2 consumption to carbonate dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…Although its contribution to the annual soil carbon budget is small on medium-to long-time scales (Kuzyakov, 2006), it has been shown that on short-time scales (hourly-daily), the equilibrium of these reactions can be very dynamic explaining, under certain circumstances, diurnal patterns of soil CO 2 exchange (Roland et al, 2013). Using a geochemical model to calculate weathering rates in a shrubland site in the SE of Spain, Roland et al (2013) showed that weathering reactions can contribute considerably to the net ecosystem carbon balance during dry periods. As explained in this study, on carbonate substrates, changes in soil CO 2 concentration within the soil-atmosphere caused by turbulence-driven mass transport affect the equilibrium of carbonate precipitation-dissolution reactions on short-time scales.…”
Section: Pedochemical Processes Of Co 2 Exchangementioning
confidence: 99%
“…In the current literature, soil CO 2 efflux has been mostly assumed to be equivalent to soil respiration, that is, to biological activity within soils, but non-biological processes contribute to soil CO 2 efflux in many regions of the world (e.g. Rey et al, 2012a;Roland et al, 2013). Soil respiration is defined as the flux of CO 2 resulting from the biological activity of roots, microfauna and microorganisms within the soil.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the CO 2 sequestration process proposed in the current study, must have been, and will be intensified as atmospheric CO 2 concentration increases [Hamerlynck et al, 2013], in which CO 2 is pushed into saline/alkaline soil and thus the process itself must constitute a carbon sink. The temperature-driven abiotic (or inorganic, geochemical) CO 2 fluxes observed in desert [Yates et al, 2013] and karst regions [Roland et al, 2013] or Antarctic dry valleys [Shanhun et al, 2012] should also contribute significantly to diurnal, seasonal, or even interannual variations in the global carbon cycle. Overall, we believe that nonbiological processes in the modern global carbon cycle may have been greatly underestimated and further study of these processes is highly warranted.…”
Section: 1002/2015gl064222mentioning
confidence: 99%